Pulmonary route of administration is instrumental in developing therapeutic interventions against respiratory diseases - Xue Jin; Ling Song; Chao-Chao Ma; Yan-Chun Zhang; Shui Yu (Saudi Pharmaceutical Journal)
Pulmonary route of drug delivery has drawn significant attention due to the limitations associated with conventional routes and available treatment options. Drugs administered through pulmonary route has been an important research area that focuses on to developing effective therapeutic interventions for asthma, chronic obstructive pulmonary disease, tuberculosis, lung cancer etc. The intravenous route has been a natural route of delivery of proteins and peptides but associated with several issues including high cost, needle-phobia, pain, sterility issues etc. These issues might be addressed by the pulmonary administration of macromolecules to achieving an effective delivery and efficacious therapeutic impact. Efforts have been made to develop novel drug delivery systems (NDDS) such as nanoparticles, microparticles, liposomes and their engineered versions, polymerosomes, micelles etc to achieving targeted and sustained delivery of drug(s) through pulmonary route. Further, novel approaches such as polymer-drug conjugates, mucoadhesive particles and mucus penetrating particles have attracted significant attention due to their unique features for an effective delivery of drugs. Also, use of semi flourinated alkanes is in use for improvising the pulmonary delivery of lipophilic drugs. Present review focuses on to unravel the mechanism of pulmonary absorption of drugs for major pulmonary diseases. It summarizes the development of interventional approaches using various particulate and vesicular drug delivery systems. In essence, the orchestrated attempt presents an inflammatory narrative on the advancements in the field of pulmonary drug delivery.